Celebrity vs. influencer endorsements: how commodity organizations can influence consumer behavioral intention change - Rourke, Creigh Alice (Kansas State University, 2023)
Two important goals of commodity organizations are increasing consumer demand and education. One way to meet these goals is through the use of endorsers, such as celebrities and influencers. Historically, commodity organizations have used celebrities to reach consumers, and recently, organizations have also been engaging in influencer marketing. Research surrounding the use of influencers by the agricultural industry is limited, and no studies have identified the outcomes of using celebrities and influencers in this context. This study sought to determine how endorsement type impacted consumer attitude, if endorsement type impacted consumer intention to purchase a commodity product and visit a commodity organization’s website, and if the perceived source credibility was greater for an influencer endorser than a celebrity endorser. The theoretical framework used to guide this study was Multi-Step Flow Theory, opinion leadership, and Theory of Planned Behavior. Multi-Step Flow Theory explains the flow of communication from media to the public. Opinion leaders, also known as endorsers in this study, serve as a mediator of information in this flow of communication. Theory of Planned Behavior helped explain an individual's behavior and the factors leading to intent to perform a certain behavior. This study’s research questions were addressed using a quantitative between-subjects experimental research design. A Qualtrics questionnaire instrument was distributed to Kansas State University undergraduate students on the Manhattan, Kansas campus. Embedded in the instrument, the manipulation was three mock Instagram posts, in which the independent variable differed by endorsement type (celebrity, influencer, control). The dependent variables were consumer attitude toward the endorsement, behavioral intention to purchase a commodity product, behavioral intention to visit a commodity organization’s website, and perceived source credibility of the endorsement. Individual difference variables measured were demographics; current behaviors related to pork consumption, pork purchasing, and website visiting; social media use; agricultural disposition; endorsement susceptibility; subjective norms related to pork consumption, pork purchasing, and website visiting; and perceived behavioral control related to pork consumption, pork purchasing, and website visiting. Results of the study revealed there were no statistically significant differences between the celebrity endorsement and the influencer endorsement in attitudes toward the endorsement, behavioral intention to purchase a commodity product, or behavioral intention to visit a commodity organization. There was a statistically significant difference between the perceived source credibility of the control endorsement and the influencer and celebrity endorsement. Future research should include investigating why a non-descript person had a greater perceived source credibility than an influencer and celebrity. This study confirmed research on influencer marketing in food and agriculture should continue to expand to better understand the nuances of the endorser types best suited for meeting commodity organization goals.
Keywords: Influencer marketing; Celebrity endorsement; Multi-step flow theory; Opinion leadership; Theory of planned behavior; Commodity organizations